Perkawinan Sedarah di Desa Ruteng Pu’u Kecamatan Langke Rembong Kabupaten Manggarai Tengah Provinsi Nusa Tenggara Timur - Ratna Kusuma Mahardika; I Nyoman Suarsana; Ni Luh Arjani (Sunari Penjor : Jurnal of Anthropology, 2021)
Talking about marriage is quite broad, let alone explaining the term marriage itself, marriage itself is closely related to culture and religion, as in the marriage system of the Manggarai Tribe. Marriage of the Furnace, Marriage of the Furnace, is a marriage between the children of brothers and sisters which is the subject of local religious debate. This paper aims to find out: a) why the marriage of the stove in the Ruteng Pu'u community still exists b) the implications of the marriage of the stove with the legitimacy of the church and state in the lives of the people in the village of Ruteng Pu'u, Central Manggarai Regency, East Nusa Tenggara. The support of Robert K Merton's theory of qualitative research methods which include observation, interviews, literature studies, analysis of research results shows that furnace mating is still carried out by the younger generation, but was not selected in the past because there were many conflicts with local religions.